Alendronate modified mPEG-PLGA nano-micelle drug delivery system loaded with astragaloside has anti-osteoporotic effect in rats. (31st December 2022) - Xi, Yanhai; Wang, Weiheng; Ma, Liang; Xu, Ning; Shi, Changgui; Xu, Guohua; He, Hailong; Pan, Wenming
Abstract: Astragaloside (AS) has an anti-osteoporotic effect, but its poor water solubility and low bioavailability limit its application. In this study, a novel nano-carrier with bone targeting was prepared by modifying mPEG-PLGA with alendronate (AL) before incorporation into astragaloside nano-micelles (AS-AL-mPEG-PLGA) to enhance the oral bioavailability, bone targeting and anti-osteoporosis effect of AS. The release behavior of AS-AL-mPEG-PLGA in vitro was investigated via dialysis. The pharmacokinetics of AS-AL-mPEG-PLGA was studied in Sprague-Dawley (SD) rats. The cytotoxicity of AS-AL-mPEG-PLGA in vitro (via MTT method), coupled with bone targeting ability in vitro and in vivo were evaluated. The therapeutic effects of free AS and AS-AL-mPEG-PLGA (ELISA, micro-CT, H&E staining) were compared in osteoporotic rats. AS-AL-mPEG-PLGA with smaller particle size (45.3 ± 3.8 nm) and high absolute zeta potential (−23.02 ± 0.51 mV) were successfully prepared, wherein it demonstrated higher entrapment efficiency (96.16 ± 0.18%), a significant sustained-release effect for 96 h and acceptable safety within 10–200 μg/mL. AS-AL-mPEG-PLGA could enhance the hydroxyapatite affinity and bone tissue concentration of AS. The relative bioavailability of AS-AL-mPEG-PLGA was 233.90% compared with free AS. In addition, the effect of AS in reducing serum levels of bone metabolism-related indicators, restoring the bone microarchitecture and improving bone injury could be enhanced by AS-AL-mPEG-PLGA. AS-AL-mPEG-PLGA with small particle size, good stability, remarkable sustained-release effect, safety and bone targeting was successfully constructed in this experiment to potentially improve the oral bioavailability and anti-osteoporosis effect of AS. Thus, AS-AL-mPEG-PLGA may be a promising strategy to prevent and treat osteoporosis.